Oxidative myocardial damage in human cocaine‐related cardiomyopathy. (11th February 2015) - Frustaci, Andrea; Russo, Matteo A.; Morgante, Emanuela; Scopelliti, Fernanda; Aquilano, Katia; Ciriolo, Maria R.; Grande, Claudia; Verardo, Romina; Chimenti, Cristina
<x xml:space="preserve">Abstract</x> Aims The pathogenesis of cocaine‐related cardiomyopathy (CCM) is still unclear. Oxidative damage from cocaine‐generated reactive oxygen species (ROS) overcoming myocardial antioxidant reserve has been hypothesized by experimental studies. Methods and results Ten (2.3%) of 430 consecutive cases with dilated cardiomyopathy (DCM) were attributed to CCM. Endomyocardial biopsies from CCM were retrospectively investigated with histology, electron microscopy, immunohistochemistry (graded 0–3), and Western blot analysis for inducible nitric oxide synthase (iNOS) and nitrotyrosine. Oxidative damage to DNA was investigated by immunostaining for 8‐hydroxydeoxyguanosine (8‐OHdG), while apoptosis and necrosis were evaluated by in situ ligation with hairpin probes. Myocardial anti‐oxidant reserve was evaluated through assessment of superoxide dismutase (SOD1‐2) and catalase (CT) activity in two frozen samples from each patient. Results were compared with idiopathic DCM and normal controls. Cardiomyocytes were bigger and myocardial fibrosis was more pronounced in CCM than in the DCM cohort. Contraction band necrosis was always detectable only in CCM with sparse lymphocytic infiltrates in three cases. Both iNOS and nitrotyrosine were significantly more expressed in CCM than in DCM. Immunostaining for 8‐OHdG, cardiomyocyte apoptosis, and necrosis were significantly increased in CCM compared with controls and DCM. Myocardial SOD1 and CT activity was significantly decreased compared with DCM and controls, and correlated with cell death and severity of left ventricular dysfunction. Conclusion Oxidative stress is a major mechanism of myocardial damage in human CCM. It concurs with calcium overload to myocyte dysfunction and death.